IDENTIFY USE OF EDP TO STRENGTHEN STUDENT'S CRITICAL THINKING ABILITY THROUGH LKS - Moch. Bachrul Ulum; Pramudya Dwi Arista Putra; Lailatul Nuraini (Program Studi Pendidikan IPA FKIP Universitas Jember, 2021)
LKS is a teaching material that is often used by teachers in the learning process. Teaching and learning science based on the Engineering Design Process can train thinking processes well. This study aims to determine how the role of EDP is to strengthen students' critical thinking skills. This type of research is qualitative research using a single case study approach. This research was conducted at SMAN Arjasa, Jember Regency with 6 students as participants. Data were collected by observation, interviews, and documentation. Data analysis used interactive model analysis by Miles and Huberman. The credibility test uses the triangulation technique and member check. The results of this study are the use of EDP in student worksheets provides the strengthening of students' critical thinking skills and the most support is at the define, learn, and plan stages. Meanwhile, at the try, test, and decide stages are the results of developing information that has been obtained in the previous stage but with consideration of joint decisions.